Development and validation of lean body mass prediction equations for male children aged. 12 - 14 years - Cândido Simões Pires-Neto; Renato Shoei Yonamine (Universidade Federal de Santa Catarina, 2000)
The objectives of this study were: a) to develop and validate equations to estimate lean body mass of males aged 12 to 14 years old; b) to validate lean body mass equations developed by other researchers. Data were collected from 93 male children aged 12-14 years. A stepwise regression technique was used to develop all prediction equations for lean body mass. Validation analysis of the proposed equations was performed using Pearson's correlation, paired Student t test, constant error (CE) and standard error estimates (SEE). Four models were developed with bioresistance variables and one model using anthropometric variables. The multiple correlation coeffi cients (Rm) of the equations developed ranged from 0.905 to 0.965 and SEE from 2.413 kg to 1.847 kg. Validation analysis was undertaken using an independent sample of 22 children who were not part of the regression sample. In conclusion, the equations that were developed are valid for male children aged 12 to 14 years old. RESUMO Os objetivos deste estudo foram: a) desenvolver e validar equações para estimar a massa corporal magra, específica para meninos de 12 a 14 anos de idade; b) validar equações estimativas desenvolvidas por outros investigadores. Participaram do estudo 93 meninos de 12 a 14 anos. Para o desenvolvimento das equações, foi usada a técnica de regressão múltipla "passo a passo". A análise de validação das equações propostas foi realizada através de correlação simples de Pearson, teste t pareado, erro constante (EC) e erro padrão de estimativa (EPE). Foram desenvolvidos quatro modelos com variáveis de biorresistência e um com variáveis antropométricas. As correlações múltiplas (Rm) variaram de 0,905 a 0,965 e EPE de 2,413 kg a 1,847 kg. A validação foi realizada em 22 meninos que não participaram da amostra de regressão. Concluindo, as equações desenvolvidas validadas para serem usadas em meninos de 12 a 14 anos, estudantes da rede pública de Campo Grande-MS.